Pharmacokinetic and Bioequivalence Studies of Ibuprofen Suspension after a Single-dose Administration in Healthy Chinese Volunteers - Song, H.; Zhang, R.; Wei, C.; Yuan, G.; Liu, X.; Li, R.; Wang, B.; Guo, R. (Drug Research, 2013)
The aim of this study was to assessed the pharmacokinetic and bioequivalence of 2 formulations of ibuprofen suspension.20 healthy volunteers were enrolled into this random, single-dose, 2-way crossover, open-label, single-centre, pharmacokinetic study. After overnight fasting, 2 formulations (test and reference) of ibuprofen (400 mg ibuprofen/20 mL suspension) were administered as a single dose on 2 treatment days separated by a 7-day washout period. After dosing, blood samples were drawn for a period of 12 h. The plasma samples were analyzed for the presence of ibuprofen by HPLC with ultraviolet detection. Pharmacokinetic parameters were determined from plasma concentrations for both formulations.The main pharmacokinetics parameters of test and reference were as follows: t1/2 was (1.94±0.38) h and (1.95±0.28) h; Cmax was (33.41±7.83) μg · mL− 1 and (31.08±9.30) μg · mL− 1; AUC0–12 was (91.44±19.26) μg · mL−1 · h and (84.75±24.45) μg · mL−1 · h; AUC0–∞ was (92.82±19.94) μg · mL−1 · h and (85.97±24.99) μg · mL−1 · h; median Tmax was 0.5 h (range, 0.25, 2) and 0.5 h (range, 0.25, 1.5). The 90% confidence intervals of the test/reference treatment ratios for Cmax, AUC0–12 and AUC0–∞ were observed to be within the predetermined acceptable interval of 80–125%.This single-dose study in healthy Chinese fasted volunteers was shown that the ibuprofen test and reference met the requirement of the State Food and Drug Administration, and the test and reference were bioequivalent.
Keywords: ibuprofen; bioequivalence study; pharmacokinetics; HPLC